Faktor-Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita Di Wilayah Kerja Unit Pelayanan Terpadu (UPT) Puskesmas Oebobo Kupang - Erniyati Lalo (STIKes CHMK, 2018)
In infancy the usual problem is the occurrence of infectious diseases that can reduce intake of toddlers where one of the effects is stunting. Stunting is a condition characterized by chronic growth inhibition caused by long-term malnutrition. Children with a history of LBW were 5.6 times more likely to be stunting compared with children with a normal birth history (Dalimunthe, 2016). Stunting in infants is also associated with maternal age, maternal education and spending levels (socioeconomic status) in the household and history of infectious diseases. The purpose of this research is to know the factors related to stunting in toddlers in the working area of UPT Puskesmas Oebobo. This research is case control with retrospective approach. The sample is selected by simple random sampling. Number of respondents for case and control 56 respondents for toddlers with their parents. This research was conducted on April 26-May 26, 2017 in Working Area of OTOBO Puskesmas Training Unit of Kupang. Data were collected through questionnaires to parent respondents and measured their weight, height and upper arm circumference. Data analysis using Chi Square was found only birth weight, father's education level, monthly income amount and history of diseases related to stunting, while sex factor, number of household member, mother education and level of parent job no relation with stunting in toddler . The results of analysis by using multiple logistic regression found that infants with underweight birth weight at risk 19.2 times the occurrence of stunting compared to normal birth weight babies in the Working Area of Oebobo Kupang Community Health Center (UPT) Puskesmas. Keywords : stunting, factors related to stunting, Toddlers